Painting - Hodge, Anthony (New York : Gloucester Press, 1991)
Introduces portraiture, still life, landscape painting, abstract painting, and surrealism; demonstrates painting techniques; and includes examples of famous paintings.
Includes index.
Keywords: Painting -- Technique -- Juvenile literature; Painting -- Technique; Art appreciation